The Uniting Reformed Church in Southern Africa’s enactment on church judicial and legal issues - Plaatjies van Huffel, Mary Anne (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
In this article, I explore the enactment of the Uniting Reformed Church in Southern Africa on church judicial and legal issues. Part I of this article recounts the history of the Uniting reformed Church in Southern Africa. The second part of the article focuses on the legal framework and sources of the Uniting reformed Church in Southern Africa, the legal Status of the Uniting reformed Church in Southern Africa, the fundamental rights of the major and minor assemblies of the Uniting reformed Church in Southern Africa, Judicial procedures with regard to discipline, the scope of the application of Labour Law in Uniting reformed Church in Southern Africa, The Uniting reformed Church in Southern Africa and the protection of individual, the Uniting reformed Church in Southern Africa and financing. The third part of the article focuses on the Uniting reformed Church in Southern Africa enactment in the public discourse. Part IV presents two implications of my analysis, namely as a general rule that a church should dissolved properly by taking the steps required by their respective church orders or constitution. Secondly, that provision should be made in the Church Order of the Uniting reformed Church in Southern Africa on the application of Labour Law on employment relations in the Uniting reformed Church in Southern Africa.